Gambaran Klinis Gejala Covid-19 di Rongga Mulut - Shalsha Billa Ridatul Monika; Isnanto Isnanto; Hendro Suharnowo (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Introduction: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2). SARS-CoV-2 is a new type of virus. There are two types of corona viruses that can cause diseases with severe symptoms such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). Data according to WHO 2020 has confirmed the number of deaths on September 27, 2020 that cases of coronavirus (SARS-CoV-2) in the world have reached 32,730,945 cases. And it has been confirmed that the number of deaths due to the corona virus has reached 991.22 patients. Ulcerative lesions were reported in patients diagnosed with the novel coronavirus disease. This is due to the ACE2 receptor which is a cell membrane protein that is the site of attachment of the SARS-CoV-2 virus to the salivary glands. Objective: To find out the clinical picture in the oral cavity in COVID-19 patients. Methods: using literature review obtained from 3 databases, namely Pubmed, Willey Online Library, DOAJ. Results: there are several clinical features in the oral cavity in COVID-19 patients such as oral cavity lesions, erythematous, enanthem, multiple erythematous lesions, xerostomia and periodontal disease. Conclusion: The clinical picture in the oral cavity in COVID-19 patients can be seen that, COVID-19 can affect the condition of the patient's oral cavity such as oral cavity lesions, xerostomia, enanthem, erythematous, multiple erythematous lesions and necrotizing periodontal disease. This condition occurs in COVID-19 patients who are supported by various facts and patient conditions.Keywords: oral cavity; clinical manifestation; COVID-19ABSTRAKPendahuluan: Penyakit coronavirus 2019 (COVID-19) merupakan penyakit infeksi yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2). SARS-CoV-2 merupakan jenis virus baru. Ada dua jenis virus corona yang dapat menyebabkan penyakit dengan gejala berat seperti Middle East Respiratory Syndrome (MERS) dan Severe Acute Respiratory Syndrome (SARS). Data menurut WHO 2020 telah terkonfirmasi jumlah kematian pada tanggal 27 September 2020 bahwa kasus coronavirus (SARS-CoV-2) di dunia telah mencapai 32.730.945 kasus. Dan telah terkonfirmasi jumlah kematian akibar corona virus mencapai 991.22 pasien. Lesi ulseratif dilaporkan pada pasien yang didiagnosis menderita penyakit coronavirus baru. Dikarenakan reseptor ACE2 yang merupakan protein membrane sel yang menjadi tempat perlekatan virus SARS-CoV-2 pada kelenjar saliva. Tujuan: mengetahui gambaran klinis di rongga mulut pada pasien COVID-19. Metode: menggunakan literature review yang diperoleh dari 3 database yaitu Pubmed, Willey Online Library, DOAJ. Hasil: terdapat beberapa gambaran klinis di rongga mulut pada pasien COVID-19 seperti Lesi rongga mulut, Erimatosa, Enanthem, Lesi eritema multiple, Xerostomia dan Penyakit periodontal. Kesimpulan: Gambaran klinis di rongga mulut pada pasien COVID-19 dapat diketahui bahwa, COVID-19 dapat mempengaruhi kondisi rongga mulut pasien seperti lesi rongga mulut, xerostomia, enanthem, eritematosa, lesi eritema multiple dan penyakit nekrosis periodontal. Kondisi ini terjadi pada pasien COVID-19 yang didukung dengan berbagai fakto dan kondisi pasien.Kata kunci: rongga mulut; manifestasi klinik; COVID-19